Reduction of Remazol Brilliant Blue-R Dye Levels Through Electrocoagulation Process at Laboratory Scale to Reduce Pollution Levels of Textile Industrial Waste in River Streams - Sholichin, Moh.; Ismuyanto, Bambang; Saptati N. H., A. S. Dwi; Susilo, H. (The Journal of Experimental Life Science, 2023)
The textile industry produces liquid waste, which is the main cause of pollution in rivers. Textile industry wastewater has a dye content of about 40%. Electrocoagulation is one method that is able to reduce waste by using electrolysis reactions. This study aims to analyze the level of the electrode plan’s capability to reduce the level of dye waste pollution from the industry on a laboratory scale. The submerged electrode material was 7 cm x 8 cm, 7 cm x 10 cm, and 7 cm x 12 cm in dimensions. The electrocoagulation process was run for 120 minutes with a voltage of 30 volts and stirring at 200 rpm. Samples were taken at 0, 5, 15, 30, 45, 60, and 120 minutes for the electrocoagulation process. Determination of the maximum wavelength of Remazol Brilliant Blue-R was carried out by measuring 60 ppm of Remazol Brilliant Blue solution at various wavelengths in the range of 400 - 800 nm with 1 nm intervals. Measurements were carried out using a UV-Vis spectrophotometer. First-order and second-order reaction kinetics models were used to study the reaction kinetics of the Remazol Brilliant Blue-R electrocoagulation process. The highest efficiency in the Remazol Brilliant Blue-R reduction process was obtained at 86% at 120 minutes. The kinetics of the Remazol Brilliant Blue-R electrocoagulation process using aluminum-based electrodes was under the first order with an R2 value > 0.96. Keywords: Electrocoagulation, Industrial Wastewater, Remazol Brilliant Blue-R, UV-Vis Spectrophotometer.